Butyrolactone signalling circuits for synthetic biology. (October 2015) - Biarnes-Carrera, Marc; Breitling, Rainer; Takano, Eriko
Graphical abstract: Highlights: γ-Butyrolactone (GBL) hormones regulate antibiotic production in many Streptomyces species. GBL-based systems could be used to design orthogonal switches in synthetic biology. The GBL receptor ScbR has been used in mammalian synthetic switches. The chemical diversity of GBLs could be used for multi-input/multi-channel devices. Understanding natural GBL circuit complexity will guide the design of new systems. Abstract : Signalling circuits based on quorum sensing mechanisms have been popular tools for synthetic biology. Recent advances in our understanding of the analogous systems regulating antibiotics production in soil bacteria suggest that these might provide useful complementary tools to increase the complexity of possible circuit designs. Here we discuss the diversity of these natural circuits, which use γ-butyrolactones (GBLs) as their main inter-cellular signal, highlighting the range of new building blocks they could provide, as well as a number of exciting recent applications of GBL-based circuits in heterologous systems. We conclude by presenting examples of the novel circuit complexity that could become accessible through the use of GBL-based designs.